Extending the research orientation and agenda for international and comparative studies in Catholic education. Issue 2 (3rd July 2019) - D'Agostino, T.J.; Carozza, Paolo G.
Abstract : This article contributes to a discussion about building a research agenda for the international and comparative study of Catholic education. Globally, the Catholic Church's work in education represents by far the largest civil society organisation running schools and an institution of enormous historical and persistent importance in the shaping of school systems throughout the world. Yet it has been studied far too little, and so remains relatively invisible and ignored in many circles. In this essay we offer orientating considerations about the field of research on Catholic education before delving into an analysis of how to strengthen and reorient this work. Drawing upon this analysis, we share a proposed research agenda that is guiding our efforts at the University of Notre Dame, and elsewhere and discuss ideas for advancing the field.